Balancing Extrinsic and Intrinsic Rewards for Employee Performance in China’s EV Industry - Liu Yang; Jirapong Ruanggoon; Noppawan Wisedsind (Journal of Frontier in Economic and Management Research, 2025)
Employee performance is widely regarded as a cornerstone of organizational success, and in fast-changing industries it becomes even more critical. China’s electric vehicle (EV) sector exemplifies this challenge, where rapid innovation and intense competition require companies to motivate employees for both immediate efficiency and long-term commitment. This study explores how extrinsic rewards include bonuses, gifts, promotions, benefits, and intrinsic rewards, including recognition, career development, learning opportunities, and responsibility, influence task and contextual performance. A quantitative design was employed, using survey data and statistical analyses to test the proposed framework. The findings show that both extrinsic and intrinsic rewards significantly enhance performance but operate differently. Extrinsic rewards are more closely linked to short-term improvements, while intrinsic rewards foster deeper engagement and sustained contributions. By combining Herzberg’s Two-Factor Theory and Self-Determination Theory, the study demonstrates that effective reward systems must balance financial incentives with psychological motivators. The results provide theoretical contributions and practical guidance for managers seeking to strengthen motivation, build resilience, and promote sustainable performance.